Management of Gummy Stem Blight (Black Rot) on Cucurbits in Florida - Mathews L. Paret; Nicholas S. Dufault; Mason Newark; Joshua H. Freeman (EDIS)
Gummy stem blight (GSB) is a major disease of many cucurbits, including watermelon, cantaloupe, cucumber, pumpkin, squash, muskmelon, and other melons. The disease is also known as black rot due to its characteristic appearance on infected fruits. Learn the symptoms, causal agent and disease spread, and fungicides labeled for use in Florida. Updated August 2018